2016
DOI: 10.1111/wrr.12429
|View full text |Cite
|
Sign up to set email alerts
|

Role of annexin gene and its regulation during zebrafish caudal fin regeneration

Abstract: The molecular mechanism of epimorphic regeneration is elusive due to its complexity and limitation in mammals. Epigenetic regulatory mechanisms play a crucial role in development and regeneration. This investigation attempted to reveal the role of epigenetic regulatory mechanisms, such as histone H3 and H4 lysine acetylation and methylation during zebrafish caudal fin regeneration. It was intriguing to observe that H3K9,14 acetylation, H4K20 trimethylation, H3K4 trimethylation and H3K9 dimethylation along with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 39 publications
(40 reference statements)
0
28
0
Order By: Relevance
“…Some of the genes detected in the present study have already been implicated in studies of teleost fish fin regeneration and morphogenesis (see details in Table 1 ). These include anxa2a , a member of the annexin family 36 , two angiopoietic protein encoding genes, angptl5 and angptl7 11 , 37 , dpysl5a , which encodes a member of the Collapsin response mediator protein (CRMP) family 38 , and c1qtnf5 , encoding a basement membrane component 39 . Some other members of the gene network are not directly indicated in fin regeneration but appeared to have related functions in vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the genes detected in the present study have already been implicated in studies of teleost fish fin regeneration and morphogenesis (see details in Table 1 ). These include anxa2a , a member of the annexin family 36 , two angiopoietic protein encoding genes, angptl5 and angptl7 11 , 37 , dpysl5a , which encodes a member of the Collapsin response mediator protein (CRMP) family 38 , and c1qtnf5 , encoding a basement membrane component 39 . Some other members of the gene network are not directly indicated in fin regeneration but appeared to have related functions in vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, loss-of-function studies demonstrated that H3K27me3 demethylase KDM6B.1 is necessary for the process of fin regeneration in zebrafish [ 41 ]. Furthermore, genes encoding histone methyltransferases and acetyltransferases, in addition to histone modifications H3K9me2, H4K20me3, H3K4me3, and H3K14Ac, are differentially regulated or modified in this process [ 41 , 42 ]. On the other hand, an Ezh2-deficient zebrafish line depicts defective spinal cord regeneration, suggesting that H3K27me3 and Ezh2 are important in this regenerative process [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it should be recognized that the regulation of genome expression may represent an even more important determinant of function than the protein products themselves. Thus noncoding RNA and epigenetic influences on annexin expression (Wang et al, 2013;Bae et al, 2015) also warrant greater attention and may be particularly relevant in special cases such as the copy number variants of annexins A8 in human or A1 in species with special capabilities such as limb regeneration (Saxena et al, 2016).…”
Section: Discussionmentioning
confidence: 99%